2001
DOI: 10.1073/pnas.98.3.1024
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of endostatin with integrins implicated in angiogenesis

Abstract: Endostatin, a fragment of collagen XVIII, is a potent antagonist of angiogenesis and inhibitor of tumor growth in mouse models. At present, the mechanism of action of endostatin is unknown. We show here that recombinantly produced human endostatin interacts with ␣5and ␣v-integrins on the surface of human endothelial cells. We further demonstrate that the endostatin-integrin interaction is of functional significance in vitro, as we found that immobilized endostatin supports endothelial cell survival and migrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
195
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 372 publications
(211 citation statements)
references
References 48 publications
14
195
0
Order By: Relevance
“…This has been demonstrated for endostatin (Rehn et al, 2001), angiostatin (Tarui et al, 2001), thrombospondin-1 (for a review, see Bornstein, 2001) and tumstatin (Maeshima et al, 2000). Indeed, when molecules such as angiostatin Mauceri et al, 1998), endostatin (Hanna et al, 2000) or neutralising anti-human VEGF 165 antibodies (Gorski et al, 1999;Lee et al, 2000) are administered together with ionising radiation, the cytotoxic effects of the latter upon endothelial cells are potentiated in vivo, resulting in an enhanced antitumoral effect.…”
Section: Discussionmentioning
confidence: 73%
“…This has been demonstrated for endostatin (Rehn et al, 2001), angiostatin (Tarui et al, 2001), thrombospondin-1 (for a review, see Bornstein, 2001) and tumstatin (Maeshima et al, 2000). Indeed, when molecules such as angiostatin Mauceri et al, 1998), endostatin (Hanna et al, 2000) or neutralising anti-human VEGF 165 antibodies (Gorski et al, 1999;Lee et al, 2000) are administered together with ionising radiation, the cytotoxic effects of the latter upon endothelial cells are potentiated in vivo, resulting in an enhanced antitumoral effect.…”
Section: Discussionmentioning
confidence: 73%
“…Both endostatin and thrombospondin-1 present proapoptotic activity when present in soluble form, but support EC adhesion and survival when immobilized. [38][39][40] Figure 5 ISM interacts with AACs in mitochondria and blocks ATP transport from mitochondria to cytosol. (a) rISM co-IP with AACs in mitochondrial fraction of HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidences suggested that endostatin/ C18 may promote, instead of abolish, angiogenic processes. [29][30][31] Free, soluble endostatin was demonstrated to inhibit angiogenesis, whereas immobilized form of endostatin supports the survival and migration of endothelial cells. 29,30 Besides, studies on C18-null mice indicated that C18 is essential for angiogenesis in the eyes.…”
Section: Discussionmentioning
confidence: 99%
“…[29][30][31] Free, soluble endostatin was demonstrated to inhibit angiogenesis, whereas immobilized form of endostatin supports the survival and migration of endothelial cells. 29,30 Besides, studies on C18-null mice indicated that C18 is essential for angiogenesis in the eyes. 31 Given the complexity of endostatin production and function, future studies are warranted to delineate the mechanism underlying endostatin/C18 upregulation during HCC progression.…”
Section: Discussionmentioning
confidence: 99%